Efeito da água de criação larval na oviposição de Aedes aegypti em laboratório Effect of larval rearing water on Aedes aegypti oviposition in the laboratory - Lígia Leandro Nunes Serpa; Simone D'Cara Barbosa Monteiro; Júlio Cesar Voltolini (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
Para avaliar a influência da água de criação larval na oviposição de Aedes aegypti, quatro tipos de águas foram oferecidos a fêmeas grávidas. Foram observados mais ovos na água de criação larval mista (2.837) do que na água de Aedes albopictus (690) e controle (938) porém, semelhante à Aedes aegypti (2.361). To evaluate the influence of larval rearing water on Aedes aegypti oviposition, four types of water were provided for gravid females. It was observed that more eggs were laid in the mixed larval rearing water (2,837) than in the Aedes albopictus water (690) or control water (938), but that this number was similar to what was seen in the Aedes aegypti water (2,361).